Challenges of teachers when teaching sentence-based mathematics problem-solving skills - Ling, Albert Nguong Baul; Mahmud, Muhammad Sofwan (Frontiers in Psychology, 2023)
Sentence-based mathematics problem-solving skills are essential where the skills can improve the skills of dealing with various mathematical problems in daily life, increase imagination, develop creativity, and develop an individual's comprehension skills. However, mastery of these skills among students is still unsatisfactory. Therefore, this study was conducted to identify the challenges that mathematics teachers face in teaching sentence-based mathematics problem-solving skills and the approaches used in addressing those challenges. This study was conducted qualitatively in the form of a case study. The data was collected through observations and interviews with two respondents who teach mathematics year 4 in a Chinese national primary school in Kuala Lumpur. This study shows that teachers faced three challenges which are low mastery skills in students, insufficient teaching time, and lack of ICT infrastructure. Teachers addressed these challenges with creativity and enthusiasm in diversifying teaching approaches to face the challenges and developing interest and skills in solving sentence-based mathematics problems among year four students. These findings allow mathematics teachers to understand the challenges faced while teaching sentence-based mathematics problem-solving in depth to deliver quality education for every student. Nevertheless, further studies involving many respondents are needed to understand the problems or challenges of different situations and approaches that can be used in teaching sentence-based mathematics problem-solving skills.